AUTOSAR Classic vs. AUTOSAR Adaptive: A Comparative Analysis in Stack Development - Shajahan, Mohamed Ali; Richardson, Nicholas; Dhameliya, Niravkumar; Patel, Bhavik; Anumandla, Sunil Kumar Reddy; Yarlagadda, Vamsi Krishna (Engineering International, 2019)
This study aims to clarify the advantages, disadvantages, and implications of the AUTOSAR Classic and AUTOSAR Adaptive frameworks for stack development in the automotive software engineering domain. The study’s primary goals are to examine the design concepts, performance traits, development processes, and implementation difficulties of the AUTOSAR Classic and AUTOSAR Adaptive frameworks. The methodology consists of a thorough literature evaluation, an analysis of market trends, a look at development workflows, and case studies highlighting implementation issues and their resolutions. The key findings show how the AUTOSAR Classic and AUTOSAR Adaptive frameworks differ in architecture, performance, resource usage, and development process. Recommendations for standardization, funding for education and training, R&D, and regulatory frameworks are among the policy implications that support the uptake and advancement of AUTOSAR technologies in automotive software engineering. This report is an invaluable resource for those involved in the automotive sector, legislators, and industry associations trying to make sense of the complicated world of stack development and mold the course of automotive software engineering.